2022
DOI: 10.3847/2041-8213/ac49e9
|View full text |Cite
|
Sign up to set email alerts
|

The Chaotic History of the Retrograde Multi-planet System in K2-290A Driven by Distant Stars

Abstract: The equator of star K2-290A was recently found to be inclined by 124° ± 6° relative to the orbits of both its known transiting planets. The presence of a companion star B at ∼100 au suggested that the birth protoplanetary disk could have tilted, thus providing an explanation for the peculiar retrograde state of this multi-planet system. In this work, we show that a primordial misalignment is not required and that the observed retrograde state is a natural consequence of the chaotic stellar obliquity evolution … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…A stellar companion, K2-290 B (projected separation ≈110 au), was also detected and appears capable of tilting the protoplanetary disk but not capable of tilting the system today. This system is probably the best known candidate for a primordial misalignment, although a recent study by Best & Petrovich (2022) suggested an alternative possibility: The third known star in that system, K2-290 C (projected separation ≈2500 au) might have been responsible for the misalignment.…”
Section: Primordial Misalignmentmentioning
confidence: 98%
“…A stellar companion, K2-290 B (projected separation ≈110 au), was also detected and appears capable of tilting the protoplanetary disk but not capable of tilting the system today. This system is probably the best known candidate for a primordial misalignment, although a recent study by Best & Petrovich (2022) suggested an alternative possibility: The third known star in that system, K2-290 C (projected separation ≈2500 au) might have been responsible for the misalignment.…”
Section: Primordial Misalignmentmentioning
confidence: 98%
“…To explain the misalignments, for the K2-290 system it has been suggested that the outer star K2-290 B (projected separation of 110 au) could have tilted the protoplanetary disk of K2-290 A, causing K2-290 b and c to form coplanar in an initially misaligned disk (Hjorth et al 2021). An alternative formation scenario was suggested by Best & Petrovich (2022), in which the third star in the triple system, K2-290 C (projected separation of 2500 au), could be responsible for the misalignment of both planets through gravitational perturbations at much longer timescales (typically 100 Myr). For the HD 3167 system, Bourrier et al (2021) suggest that the perpendicular architecture likely arose from the outer planet being tilted through gravitational interactions with a possible outer companion, while the inner ultrashort period planet likely retained a low obliquity due to tight tidal-coupling with the host star.…”
Section: Obliquities As a Function Of Agementioning
confidence: 99%
“…The presence of an additional giant planet can further induce secular resonances (Bazsó & Pilat-Lohinger 2020) or high-e migration (Hamers 2017;Hamers & Tremaine 2017) interior to the giant planet, planet-planet scattering, and push the surviving planet into high-eccentricity orbits which could be further boosted by Kozai-Lidov cycles from the stellar companion (Mustill et al 2021). Wide-orbit stellar companion(s) can also be sufficient to explain stellar spin-planetary orbit misalignment even if the companion is orders of magnitude more distant, including inducing retrograde obliquities (Best & Petrovich 2022).…”
Section: Motivation: Substellar Companions In Wide Binariesmentioning
confidence: 99%